Evolução da tutela sumária no direito brasileiro: a estabilização da tutela antecipada e seu diálogo com o contraditório e a coisa julgada material - Alexandre Rodrigues de Sousa (2017)
The right to judicial protection based on summary cognition constitutes one of the elements of Brazilians constitutional model of process and is essential for the provision of a timely and adequate judicial protection of rights. The development of these judicial procedures has reached a stage of untying between judicial protection based on summary cognition and a procedure of an ordinary character, based on a wide cognition technique (autonomous summary procedure). It allowed, therefore, a quick response by the jurisdiction to certain types of litigation, through a lower degree of cognition, to regulate the conflict in a peremptory manner, provided that under the disinterest of the parties involved in the pursuit of the process. The present research resorts to bibliographical and documental sources to investigate the limits of application of a summary cognition technique in judicial procedures regarding its conciliation with Brazilian constitutional guarantees, especially the contradictory and the res judicata (claim preclusion).